Effect of squid pen chitooligosaccharide in conjugation with different modified atmospheric packaging conditions on color and storage stability of tuna slices. (July 2021) - Singh, Avtar; Benjakul, Soottawat; Zhang, Bin; Deng, Shanggui; Mittal, Ajay
Abstract: Effect of squid pen chitooligosaccharide (COS) at different concentrations (0, 400, and 800 ppm) on the discoloration and quality changes in yellowfin tuna ( Thunnus albacares ) slices packed under modified atmospheric packaging (MAP) using oxygen, argon or their mixture at 4 °C up to 9 days was investigated. Tuna slices packed with oxygen-based MAP in the presence of 400 ppm COS (C4-OXY) showed the lowest reduction in oxymyoglobin (oxyMb) and a* value (redness). This coincided with the lowest formation of metmyoglobin (metMb) than other samples (p < 0.05). Additionally, C4-OXY sample showed lower total viable count and lipid oxidation than the remaining samples (p < 0.05). However, argon-based MAP had no positive effect in retaining the quality of tuna slices. Nevertheless, COS at a high concentration (800 ppm) decreased the redness of tuna slices, especially those packed under argon-based MAP. COS generally lowered the oxidation of fatty acids of C4-OXY sample, as indicated by higher polyunsaturated fatty acids content than that of control sample (without COS treatment and kept in air). Overall, COS at 400 ppm in combination with oxygen-based MAP effectively reduced the metMb formation and maintained the redness of slices and prolonged shelf-life of slices with sensory acceptability at 4 °C for 9 days. Highlights: Chitooligosaccharide (COS) and modified atmosphere packaging were used in tuna meat. COS (400 ppm) and oxygen-based MAP (C4-OXY) maintained the redness of tuna slices. C4-OXY sample had the lowest metmyoglobin (metMb) content throughout the storage. Argon-based MAP had no positive impact on maintaining the color of tuna slices. Tuna in oxygen-based MAP without COS had higher lipid oxidation and metMb content.